Meat processing wastewater Phycoremediation by Botryococcus sp.: a biokinetic study and a techno-economic analysis - Abirama V.; Mohamed R.M.S.R.; Al-Gheethi A.; Abdul Malek M.; Kassim A.H.M. (Bellwether Publishing, Ltd., 2023)
Chemical operations; Nutrients; Separation; Biokinetic coefficients; Biokinetic models; Botryococcus sp; Growth factor; Meat processing; Phycoremediation; Removal efficiencies; Techno-Economic analysis; Economic analysis